2005
DOI: 10.1038/oby.2005.118
|View full text |Cite
|
Sign up to set email alerts
|

High‐density Lipoprotein Apolipoprotein A‐I Kinetics in Obesity

Abstract: OOI, ESTHER M. M., GERALD F. WATTS, MARYAM S. FARVID, DICK C. CHAN, MICHAEL C. ALLEN, SIMON R. ZILKO, AND P. HUGH R. BARRETT. Highdensity lipoprotein apolipoprotein A-I kinetics in obesity. Obes Res. 2005;13:1008 -1016. Objective: Low plasma concentrations of high-density lipoprotein (HDL)-cholesterol and apolipoprotein A-I (apoA-I) are independent predictors of coronary artery disease and are often associated with obesity and the metabolic syndrome. However, the underlying kinetic determinants of HDL metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…3B). The who are overweight or obese ( 44 ). The total protein pool sizes for the other proteins were ‫ف‬ 10-fold (apoE, apoM, apoA-II, apoC-III) to 100-fold (apoD, apoA-IV) smaller than total apoA-I, as shown previously ( 43 ).…”
Section: Apolipoprotein Peptides For Hr/am-prmsupporting
confidence: 65%
See 1 more Smart Citation
“…3B). The who are overweight or obese ( 44 ). The total protein pool sizes for the other proteins were ‫ف‬ 10-fold (apoE, apoM, apoA-II, apoC-III) to 100-fold (apoD, apoA-IV) smaller than total apoA-I, as shown previously ( 43 ).…”
Section: Apolipoprotein Peptides For Hr/am-prmsupporting
confidence: 65%
“…Consequently, the sample loss correction factor determined for apoA-I was applied to the remaining six apolipoproteins. The total apoA-I pool size was 4,897, 3,521, and 3,630 mg for participants 250, 225, and 243, respectively, the expected apoA-I pool size range for individuals with low HDL-C and who are overweight or obese ( 44 ). Separating total apoA-I into the fi ve HDL size fractions showed that the majority of apoA-I (>65%) resides in the ␣ 2 and ␣ 3 pools.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the apoA-I FCR and production rate were significantly associated with apoA-I concentration. Nonetheless, some caveats must be considered in the report: the analysis did not include equal numbers of male and female subjects, subjects with different levels of insulin sensitivities were grouped together, studies using monocompartmental or multicompartmental modeling were included, and studies carried out under fasting and postprandial conditions were grouped together (45).…”
Section: Hdl Kinetics Studies In Humans With Common Low Hdl-c Disordersmentioning
confidence: 99%
“…In humans, approximately 20% of circulating cholesterol is normally transported in high-density lipoprotein (HDL) (Attie 2007). Plasma HDL cholesterol (HDL-C) concentrations have an inverse relationship with the risk of CHD (Sasahara et al 1997;Ooi et al 2005;Van Gaal et al 2006). Reduced plasma HDL-C concentrations by ∼15%-30% compared with normal subjects are associated with obesity and obesity-related disorders such as insulin resistance, metabolic syndrome, and type 2 diabetes (Gordon et al 1977(Gordon et al , 1989Krauss 2004;Ooi et al 2005;Perségol et al 2007), which may contribute in 1 way to the increased risk for CHD in the obese and diabetic population.…”
Section: Introductionmentioning
confidence: 99%
“…For this process, nascent HDL is necessary to take up excess cholesterol from the extrahepatic tissues. Nascent HDL formation begins as a discoidal structure known as nascent or pre-β HDL, consisting of the major protein constituent apolipoprotein A-I (apoA-I), phospholipids, and free cholesterol (Ooi et al 2005;Singaraja et al 2006), consequent to the interaction of apoA-I and ATP-binding cassette transporter A-1 (ABCA1). ABCA1 mediates the efflux of cellular phospholipids and free cholesterol to extracellular acceptors, namely lipid-free or lipid-poor apoA-I, producing pre-β HDL particles (Francis et al 1995;Rogler et al 1995;Brewer et al 2004;Lee and Parks 2005;.…”
Section: Introductionmentioning
confidence: 99%